Strategi Adaptasi Ekonomi Nelayan Terhadap Kenaikan Harga BBM Solar Di Pulau Bawean Kabupaten Gresik - Dhimas Haryo Prayoga; Yunaita Rahmawati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
The increase in the price of diesel fuel has made expenditures from fishing business activities greater than before, thus affecting the economic situation of fishing families on Bawean Island. Fishermen on Bawean Island are implementing economic adaptation strategies with the aim of surviving in response to rising diesel fuel prices. The research purposes is to analyze the economic adaptation strategies implemented by fishermen and analyze the impact of the economic adaptation strategies that have been implemented in dealing with rising diesel fuel prices for fishermen on Bawean Island, Gresik Regency. This thesis uses a qualitative research model with a type of field research with an empirical approach. The results of this research can be concluded that fishermen on Bawean Island apply economic adaptation strategies, including: 1) The active strategy carried out is looking for side jobs and optimizing the role of family members. 2) The passive strategy used is to reduce family expenses by getting all family members used to eating with minimal side dishes. 3) The networking strategy used by fishermen on Bawean Island is to pawn gold and borrow some money from family, neighbors, stalls or shops, and help from the Village Head. The impact of the economic adaptation strategy that has been implemented by fishermen is that they can only meet their family's basic needs, while they still have difficulty buying diesel fuel for fishing purposes.